The effects of sodium-glucose cotransporter 2 inhibitors on hepatocellular carcinoma: From molecular mechanisms to potential clinical implications - Konstantinos Arvanitakis; Theocharis Koufakis; Kalliopi Kotsa; Georgios Germanidis (Elsevier, 2022)
Hepatocellular carcinoma (HCC) occurs in the setting of prolonged liver inflammation, hepatocyte necrosis and regeneration in patients with cirrhosis. Despite the progress made in the medical management of the disorder during the past decades, the available pharmacological options remain limited, leading to poor survival rates and quality of life for patients with HCC. Sodium-glucose cotransporter 2 inhibitors (SGLT2) originally emerged as drugs for the treatment of hyperglycemia; however, they soon demonstrated important extra-glycemic properties, which led to their evaluation as potential treatments for a wide range of non-metabolic disorders. Evidence from animal studies suggests that SGLT2i have the potential to modulate molecular pathways that affect hallmarks of HCC, including inflammatory responses, cell proliferation, and oxidative stress. The impressive benefits of neurohormonal modulation observed with SGLT2i in congestive heart failure set the stage for human trials in cirrhotic ascites. However, future studies need to evaluate several aspects of the benefit to risk ratio of such a therapeutic strategy, including the co-administration with antineoplastic agents and diuretics, infections, use in hospitalized individuals, renal safety and hypovolemia. In this narrative review, we discuss the putative role of SGLT2i in the treatment of patients with HCC, starting with the mechanisms that could justify a possible benefit and ending with potential clinical implications and areas for future research.